ISLAMIC ACTIVISM IN SOCIAL MOVEMENT THEORY - Roberto Arieza Martin Purba; Yusuf Wibisono (Journal of Scientech Research and Development, 2026)
This analytical review examines Islamic Activism: A Social Movement Theory Approach (2004), edited by Quintan Wiktorowicz, with the objective of assessing its theoretical contribution, empirical relevance, and applicability to contemporary studies of political Islam, particularly in Southeast Asia and Indonesia. Employing a dual methodological approach—textual analysis and contextual evaluation—the review explores how the book integrates classical social movement theories, including resource mobilization, political opportunity structures, and framing processes, into the study of Islamic activism across diverse Muslim societies. The book argues that Islamic activism should be understood as a social and political phenomenon rather than as a purely theological or ideological expression. Through comparative case studies from Algeria, Egypt, Bahrain, Palestine, Yemen, Iran, Saudi Arabia, and Turkey, the contributors demonstrate that Islamic movements are shaped by the same social dynamics that influence other collective movements, including organizational resources, political environments, social networks, and cultural narratives. The review finds that the book successfully challenges essentialist interpretations of Islam by presenting activism as a rational, context-dependent process. Its interdisciplinary framework provides a valuable analytical lens for understanding the interaction between religion, politics, and society. Furthermore, the review highlights the continued relevance of the book in explaining contemporary developments such as Islamic philanthropy, digital da‘wah movements, civil society activism, and the transformation of political Islam in democratic contexts such as Indonesia. Nevertheless, several limitations are identified, including its limited engagement with theological dimensions, insufficient attention to gender perspectives, and the absence of digital and transnational activism analyses that have become increasingly significant in the twenty-first century. Overall, the review concludes that Wiktorowicz’s framework remains a foundational contribution to political Islam studies and social movement scholarship. Its emphasis on mobilization, political opportunities, and framing processes continues to offer a robust theoretical foundation for examining the evolving forms of Islamic activism in both authoritarian and democratic societies.